(untitled) (Journal of the College of Languages (JCL), 2021)
Stylistics is the analysis of the language of literary texts integrated within various approaches to create a framework of different devices that describe and distinct a particular work. Therefore, feminist stylistics relied on theories of feminist criticism tries to present a counter- image of a woman both in language use and society, to draw attention , raise awareness and change ways that gender represents. Feminist stylistic analysis is related not only to describe sexism in a text, but also to analyze the way that point of view, agency, metaphor, and transitivity choices are unanticipatedly and carefully connected to issues of gender(Mills,1995:1) The study tries to discuss matters of gender representation in stylistic analysis and how questions and messages of gender are deducted and exposed when reading and interpreting a text. Moreover, the concept of transitivity and how meaning is encoded and adopted by different patterns of transitivity will be analyzed and investigated. The study has shown that transitivity patterns are used as a device to analyze gender representation as well as to describe the ideational meaning which involves the experiential realization of the world. The results of the analysis of transitivity choices of the selected romantic scene have shown that the whole number of processes are nineteen, the female does five processes in her role as an actor, whereas male shows fourteen which are the highest number in his performance. The male appears to be the active participant agent who is conscious and in control of his action, whereas the female appears to be passive in her quality, volition and being affected or recipient actor. Also, it is seen that feminist analysis tries to create a new message and picture of woman position; this is depicted by the essential role of the readers’ assumption and contextual factors of the text in the process of interpretation.